Cutaneous granulomas with primary immunodeficiency in children: a report of 17 new patients and a review of the literature. (15th April 2019) - Leclerc‐Mercier, S.; Moshous, D.; Neven, B.; Mahlaoui, N.; Martin, L.; Pellier, I; Blanche, S.; Picard, C.; Fischer, A.; Perot, P.; Eloit, M.; Fraitag, S.; et al.
Abstract: Background: Paediatric cutaneous granuloma with primary immunodeficiency (PID) is a rare condition. The physiopathology is unclear, and treatment is challenging. We report on 17 paediatric cases and review the literature. Objectives: To make dermatologists and dermatopathologists aware of the diagnostic value of skin granulomas in paediatric PID. Methods: We collected data on 17 patients with cutaneous granulomas and PID registered with us and also reviewed 33 cases from the literature. Results: Cutaneous granuloma was the presenting feature of the PID in 15 of the 50 collated cases. The lesions presented as red‐brownish nodules and infiltrated ulcerative plaques, predominantly on the face and limbs. Scleroderma‐like infiltration on a single limb was observed in 10% of the cases. The associated PID was ataxia‐telangiectasia (52%), combined immunodeficiency (24%), cartilage‐hair hypoplasia (6%) and other subtypes (18%). The granulomas were mostly sarcoidal, tuberculoid, palisaded or undefined subtypes. In some patients, several different histopathologic granulomatous patterns were found in the same biopsy. Some granulomas were associated with the presence of a vaccine strain of rubella virus. Conclusion: Cutaneous granulomas associated with a PID have a variable clinical presentation. A PID can be suspected when crusty, brownish lesions are found on the face or limbs. The concomitant presence of several histological subtypes in a single patient is suggestive of a PID.